Institutional Roles and Mechanisms in Upholding Legal Protection Under Consumer Protection Law in the Era of Globalization - Wiwik Sri Widiarty; Md Hasnath Kabir Fahim (Unissula, 2024)
Consumer protection law is essential in safeguarding rights against fraud and unfair practices, relying on both private institutions and governmental enforcement. This study aims to analyze the legal frameworks of consumer protection in Indonesia. It also examines the roles of institutions in the legal enforcement of consumer protection, particularly their function in maintaining the balance of relations between consumers and producers in the context of globalization and extensive online marketing. The methodology employed is normative legal research, which examines Indonesia’s Consumer Protection Law (Law Number 8 of 1999) through the lens of key concepts such as consumer rights, the institutional roles in enforcing these rights, and ensuring fair business practices. The findings underscore the importance of various consumer protection institutions, such as National Consumer Protection Agency (Badan Perlindungan Konsumen Nasional or BPKN), Non-Governmental Consumer Protection Institution (Lembaga Perlindungan Konsumen Swadaya Masyarakat or LPKSM), Consumer Dispute Resolution Agency (Badan Penyelesaian Sengketa Konsumen or BPSK), in Indonesia, which serve to educate, supervise, and assist consumers in resolving disputes with businesses. This study also identifies the challenges in implementing consumer protection law, particularly concerning the broad range of involved institutions, as well as the need for heightened consumer awareness and greater accountability from business actors.